(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Aethes rubiginana (Walsingham, 1903) and Osthelderiella amardiana Obraztsov, 1961, two new tortricids for the European fauna, are recorded in southem ltaly. Ae. rubiginana was collected in Sicily and Calabria, while O. amardiana was found in Basilicata on Pollino mountains.